Association between school bullying victimization and self-harm in a sample of Chinese children and adolescents: The mediating role of perceived social support - Che, Yusan; Lu, Jin; Fang, Die; Ran, Hailiang; Wang, Sifan; Liang, Xuemeng; Sun, Hao; Peng, Junwei; Chen, Lin; Xiao, Yuanyuan (Frontiers in Public Health, 2022)
Background: Studies have indicated that bullying victimization is an important risk factor of self-harm in children and adolescents. However, it is yet to be studied if perceived social support significantly mediates this association. In this study we aim to examine the association between bullying victimization and self-harm, with a particular focus on the mediating role of perceived social support. Methods: A population-based cross-sectional study of 4,627 Chinese students aged 10 to 17 years was conducted in southwestern China Yunnan province. A two-stage simple random cluster sampling method was used to choose study subjects. The adjusted associations between school bullying victimization, perceived social support, and self-harm were examined by using multivariate logistic regression models. The mediation of perceived social support in the association between bullying victimization and self-harm was evaluated by using path model. Results: After controlling potential covariates, bullying victimization was associated with increased self-harm prevalence, with an adjusted odds ratio of 1.90 (95% CI: 1.57, 2.32). Among all sources of perceived social support, only parental support played a prominent mediating role in the association between bullying victimization and self-harm, accounted for 20.73% of the explained variance. The mediation of parental support was comparable between boys and girls. As for different types of bullying victimization, path analyses indicated that only the association between physical victimization and self-harm was significantly mediated by parental support. Conclusions: Our study results highlight the promising intervention benefit of parental support in bullying victimization associated self-harm risk for children and adolescents. For victims of bullying, especially physical bullying, promoting parental support might be effective in reducing self-harm risk. Longitudinal studies are warranted to further corroborate these findings.